A critical review of organic manure biorefinery models toward sustainable circular bioeconomy: Technological challenges, advancements, innovations, and future perspectives. (September 2019) - Awasthi, Mukesh Kumar; Sarsaiya, Surendra; Wainaina, Steven; Rajendran, Karthik; Kumar, Sumit; Quan, Wang; Duan, Yumin; Awasthi, Sanjeev Kumar; Chen, Hongyu; Pandey, Ashok; Zhang, Zengqiang; Jain, Archana; et al.
Abstract: Total livestock emissions account for up to 14.5% of man-made greenhouse gas emissions. Counteractive measures, such as circular economy concepts and negative emission technologies are necessary to limit global warming below 1.5 °C. Possible treatment options for organic manure include anaerobic digestion, combustion, gasification, hydrothermal liquefaction and composting. The choice of treatment varies depending on the economics, the requirement of a specific product, and sociocultural factors. Commercialization of these treatments needs a blend of appropriate technology, feasible economics, policy support and agreeable socio-cultural conditions. Key findings of this study include the following: 1. Increasing scientific awareness about manure management and treatment; 2. Building a sustainable cooperative model to commercialize technologies; 3. Creating a market for manure recycling products; 4. The role of policy in supporting technologies and consumers; and 5. The codigestion of substrates for better efficacy. Current trends show minimal actions in place as opposed to the high-rate of acceleration that is necessary. Highlights: Improper disposal of organic manure could cause unwanted ecological damage. Recent biorefinery models to recover energy and nutrients are addressed. Biological treatment of organic manure remains the predominant recycling approach. Limited knowledge of the potential of biorefinery approaches still exist. Successful implementation of biorefineries requires policy and social support.